VARIASI KONSENTRASI EMULGATOR SPAN-TWEEN 80 PADA FORMULASI KRIM BODY SCRUB EKSTRAK ETANOL DAUN SIRIH MERAH (Piper crocatum Ruiz & Pav) - Densi Selpia Sopianti (Universitas Hang Tuah, 2023)
Flavonoid compounds can act as antioxidants that can play o role in skin ejuvenation as contained in Daun sirih merah (Piper crocatum Ruiz & Pav) which is formulated in the form of body scrub cream. A good cream can be seen from the stability of the physical properties of the emulsion. Good emulsifier properties are able to form a stable oil-in-water (O/W) emulsion composition. Therefore, the purpose of this study was to determine which concentration of the formulation was the most stable of the variations in the concentration of the Span-Tween 80 emulsifier in the body scrub cream formulation of the ethanol extract of Daun sirih merah (Piper crocatum Ruiz & Pav). Extraction method uses the maceration method with 96% ethanol as solvent. Body scrub cream preparations from the daun sirih merah (Piper crocatum Ruiz & Pav) extract were made in three variations of the concentration of emulsifier span-tween 80, namely: 1%, 3%, 5% and then evaluated physically and chemically including organoleptic tests, homogeneity tests, pH tests, viscosity tests, power tests. stickiness test, daun sirih merah (Piper crocatum Ruiz & Pav) spreadability test, cream type test, hedonic test and irritation test. The results showed that from the evaluation results of the three variations in the concentration of emulsifier span-tween 80 1%, 3%, 5%, the best red betel leaf ethanol extract body scrub cream was formula 3 with a span-tween concentration of 80 5% which met all the requirements. to the stability verygood of the body scrub cream.